Deficiencies of orthodox foreign trade theory with regard to employment - Detlef Lorenz (Intereconomics, 1985)
The orthodox theory of foreign trade, which is simply a theory of re-allocation, can scarcely do justice to the issues that arise in the context of North-South relations. Its isolation from the problems of world and regional economic development, different trade flows and the transfer of production factors reduces its relevance to employment.
Keywords: 330; North-South Relations